Examining Characteristics of Opinion Leaders in Social Media: A Motivational Approach. (August 2016) - Winter, Stephan; Neubaum, German
Social networking sites offer various opportunities to express opinions on politics and public affairs and to disseminate information to a large circle of acquaintances. The present research aims to identify the characteristics of people who consider themselves as opinion leaders on these new channels, the features they use in order to influence others, and the psychological motives they pursue. A survey ( N = 527) among Facebook users identified political interest and personality strength as significant predictors of perceived Facebook opinion leadership, while the influence of extraversion was not significant. Those who write private messages on political debates do this in order to raise awareness of specific topics, while opinion expression in public status updates is also strongly connected to self-presentational goals (impression motivation). Moreover, the motives of presenting oneself positively and convincing others are particularly important for people with high personality strength. The present findings extend previous knowledge by redefining the concept of opinion leadership in new media environments and describing motivational links between individuals' predispositions and their activities to influence others' opinions. On a practical level, the pronounced role of self-presentational motives is likely to have important implications for the dynamics of public debates in social media.